A prospective study of vaginal topical pretreatment of compound sea-buckthorn oil suppository in postmenopausal women prior to colposcopy - Yi Yu; Qing Li; Yuankui Cao; Hongwei Zhang; Yu Song; Qing Cong; Long Sui; Limei Chen (Scientific Reports)
Abstract Postmenopausal women are faced with difficulties in colposcopy, such as easy bleeding from epithelial atrophy, and thinning, atypical colposcopy images, unsatisfactory exposure, and decreased sensitivity of colposcopy. We aimed to improve the sensitivity and satisfaction of colposcopy in postmenopausal women and to evaluate the clinical efficacy of compound sea-buckthorn oil suppository on topical vaginal pretreatment in postmenopausal women prior to colposcopy. Postmenopausal patients who underwent colposcopy in the Obstetrics and Gynecology Hospital of Fudan University from April 2023 to July 2024 were randomly assigned to three groups: (A) untreated control group, (B) compound sea-buckthorn oil suppository group, (C) estrogen ointment group. Group B and group C were treated for 2 weeks before colposcopy, and the colposcopy and adverse reactions were analyzed. A total of 377 patients were included in this study, of which 9 patients were excluded from the colposcopy results for failing to complete the 2-week medication, and 368 patients were included in the colposcopy results, including 125 patients in group A, 121 patients in group B, and 122 patients in group C. The high-risk HPV infection before colposcopy accounted for 94.3% (347/368), of which HPV16 and/or HPV18 infection accounted for 20.4% (75/368), and other types of infection accounted for 75.3% (277/368). The patients with abnormal cytology (ASCUS and above) accounted for 47.6% (175/368). No significant differences were observed in age, cytology before colposcopy, and HPV type among the three groups. There were 196 cases (53.3%) of abnormal pathologies in postoperative colposcopic biopsy, among which 42 cases were high-grade cervical squamous intraepithelial lesions. After 2 weeks of medication, the integrity of vaginal epithelium, the adequacy ratio of colposcopy, and the satisfaction rate of acetic acid test and iodine staining test in groups B and C were significantly improved compared with group A (P < 0.001), and there was no significant difference between groups B and C. The incidence of breast discomfort in the estrogen ointment group was 5.6%, while the incidence of dizziness and headache was 4%. In contrast, no such side effects were reported in the compound sea-buckthorn oil suppository group, and the difference was statistically significant. Additionally, there was no significant statistical difference in local vaginal adverse reactions between groups B and C. Compound sea-buckthorn oil suppositories are helpful in improving the sensitivity and satisfaction of postmenopausal women with colposcopy, reduce blind biopsies. The effects are not inferior to estrogen. Compared to estrogen ointment, compound sea-buckthorn oil suppositories are most cost-effective and have fewer side effects and can be applied in clinical practice.